1977
DOI: 10.1177/009365027700400405
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped Traits and Sex Roles in Humorous Drawings

Abstract: Cartoons are used as indicators of the social meanings, especially personality traits and emotional states, typically assigned to men and women. Single-frame cartoons relevant to sex roles were randomly sampled at five-year intervals, beginning in 1952, from Saturday Evening Post, Saturday Review, and Playboy. Statistical trend analysis on 430 cartoon people in 195 cartoons reveals more trait stereotyping for females than for males. Five dominant, general stereotypes were found: the seductive female, the sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Results were comparable to previous studies that have found males enjoy hostile humor, jokes, and cartoons more than females do (e.g., Terry & Ertel, 1974). One reason for this may be sex bias in stimuli: cartoon characters are often portrayed in sex-stereotyped situations (Anderson & Jolly, 1977), and females are often the butt of jokes. In cartoon rating studies, Chapman and Gadfield (1976) and Henkin and Fish (1986) found no gender difference in enjoyment of sexual humor that was not sexist.…”
Section: Discussionsupporting
confidence: 82%
“…Results were comparable to previous studies that have found males enjoy hostile humor, jokes, and cartoons more than females do (e.g., Terry & Ertel, 1974). One reason for this may be sex bias in stimuli: cartoon characters are often portrayed in sex-stereotyped situations (Anderson & Jolly, 1977), and females are often the butt of jokes. In cartoon rating studies, Chapman and Gadfield (1976) and Henkin and Fish (1986) found no gender difference in enjoyment of sexual humor that was not sexist.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, comic strips have been studied as a way to assess views of gender in society. For instance, Anderson and Jolly (1977) studied stereotyped traits and sex roles in cartoons from various types of magazines. Potkay, Potkay, Boynton, and Klingbeil (1982) noticed that attitudes to sex-roles were beginning to change in their study of adjective descriptions of male and female characters in comic strips.…”
Section: Comic Art In Scientific Inquirymentioning
confidence: 99%
“…Miller (1993) suggested this possibility in her analysis of cartoons about vice-presidential candidate Geraldine Ferraro, speculating that certain graphic metaphors may be intended to depict women in a positive light but instead carry opposite messages. Supporting this notion is the view stated by other researchers that male characters drawn by male cartoonists seem to be more human and realistic than corresponding female characters (Anderson and Jolly 1977;Press 1981;Sheppard 1994, 186).…”
Section: Conclusion and Discussionmentioning
confidence: 84%